Globalization and international business cycle dynamics: A conditional GVAR approach - Michael Binder; Christian J. Offermanns (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
We examine the effects of increased international integration of both goods and financial markets on business cycle dynamics. To do so, we develop a new econometric framework for modelling cross-country spillovers in which the magnitude of these spillovers is an empirically determined function of the degree of a country's integration with international goods and financial markets. Our results suggest that the magnitude of cross-country spillovers for most country pairs has been increasing with strengthened goods and financial markets integration.
Keywords: E32; F41; C33; 330; business cycle dynamics; international goods and financial market integration; dynamic panel data models; global VAR model